An Examination of the Perceptions held and Approaches used by Primary School Teachers regarding Child Neglect in urban DEIS band one schools. - McGuirk, Jennifer (My University, 2021)
Child neglect, a highly pervasive form of maltreatment, is associated with a caregiver’s omission of care. Physical, emotional, educational and/or medical neglect can impair a child’s psychological and physiological development. Such impairments are visible in primary school classrooms through a child’s appearance, academic achievements and through their presentation of internalising and/or externalising behavioural problems. The research question underpinning this investigation relates to examining the perceptions held and approaches used by primary school teachers in urban DEIS band one schools regarding issues of child neglect. In this thesis, the author comprehensively explores the current literature concerning child neglect. Researchers discuss environmental factors that may be conducive to neglect including; poverty, unemployment, educational attainment levels, sociocultural backgrounds, substance misuse, caregiver-child separation and violence. Qualitative methods of research were used in this study to explore educators’ practical experiences with issues of child neglect. Findings illustrate the increasing prevalence of child neglect in schools and classrooms and indicate how neglect is not restricted to those facing disadvantage. The study outlines how educators’ inadequate knowledge of child neglect restricts their ability to identify signs in the range of definitions of neglect. Additionally, a disconnection between schools, outside agencies and professionals is indicated in this research as problematic in prolonging action to address and support minors living in neglectful home environments. The research concludes by recommending actions that could be taken to; develop practitioners’ repertoire of knowledge regarding neglect and; introduce systemic structures to facilitate co-operation between schools, outside agencies and professionals to efficiently address incidences of child neglect.
Keywords: Child neglect; Child abuse